China may draw a sharply lower line on mobile phone radiation.
The People's Republic may impose the world's toughest mode phone radiation standard. The tighter limits could require erecting additional phone towers and reengineering entire lines of handsets. So, with the help of US and European Union authorities, manufacturers are trying to persuade China to harmonize its standards with these of the International Commission on Non-Ionizing Radiation Protection, (ICNIRP). China's draft standard would limit radiation passed from handset to user to a specific absorption rate of 1 W/kg. That is half the 2 W/kg ICNIRP limit adopted by most European nations for any 10 grams of contiguous tissue and significantly,. lower than the US standard of 1.6 W/kg for any 1 gram of contiguous tissue.
Keywords: China; European Union; International Commission on Nonionizing Radiation Protection; US standard; Handsets; Mobile phone radiation standard; Phone towers; Specific absorption rate; Tissue